Self- Spirituality and its Advantageous Impact for Positive Counselling Attitudes among Youths (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2016)
This paper presents the influences of self-spirituality for prosperous Counselling attitudes among youths with particular focus on Nigerian students in Malaysian Universities, towards becoming positive agents of change in the society. The research paper analyses ways in which self-spirituality can be applied independently as a Counselling means to achieve positive attitudes among these university students. The Null hypothesis stated that there are no significant and direct relationships between self-spirituality and counselling attitudes. To carry out the research, two instruments were combined in a quantitative survey involving 394 students that were systematically drawn from ten randomly selected universities in Malaysia. The results of the data analysis indicate the fact that self-spirituality has a positive impact on counselling attitudeswith (β =0.212 and p value = 0.002). The null hypothesis was therefore rejected. The analysis ends with a discussion that provides recommendations that can be adopted to ensure success of the self-spirituality use in counselling. The paper suggested with remarkable conclusion that since spirituality plays such an important role in every society, there should be more nurturing of it in the society while the Guidance Counsellors work towards directing the young people on the right path of God.